Trends in outpatient healthcare visits among adults aged 50 years and older in 27 European countries: analysis of population-based survey data, 2004-2022 - Nguyen, Van-Kinh; Reuter, Anna; Abd El Aziz, Mirna Safia; Bärnighausen, Till (The lancet. Regional health, 2025)
Background - Understanding trends in healthcare utilisation is key to policy and planning, especially after a prolonged pandemic that led to shutdowns of services in many societal sectors. The aim of this study is to provide comprehensive, cross-country evidence on long-term outpatient care trajectories for the older population in Europe. - Methods - We used longitudinal data from 147,116 individuals aged 50 years or older in 27 European countries from the Survey of Health, Ageing and Retirement in Europe (SHARE). We divided the data into three phases: pre-pandemic (2004-2019), pandemic (2021; 2020 excluded due to changes in data collection), and post-pandemic (2022). We used a Bayesian spatiotemporal model to analyse the number of outpatient healthcare visits by sex (male/female) over time and to establish their association with age and chronic conditions. - Findings - From 2004 to 2019, the rate of outpatient healthcare visits for a reference individual (defined as 75 years old with no chronic conditions) varied more than threefold across European countries: For men, visits were lowest in Sweden in 2004, with 1.52 [95% uncertainty interval (UI): 1.45-1.61] visits, and highest in Luxembourg in 2019, with 4.62 [4.30-4.90] visits. For women, visits were also lowest in Sweden in 2004 (1.82 [1.74-1.89]) and highest in Luxembourg in 2019 (5.60 [5.20-5.97]). During COVID-19, healthcare visits of men ranged between 0.06 [0.06-0.07] in Italy and 0.45 [0.41-0.49] in Germany, relative to the rate expected without the pandemic. For women, the relative rate ranged between 0.05 [0.05-0.06] in Italy and 0.42 [0.39-0.45] in Germany. Relative reductions were larger for older adults and those with chronic conditions. After COVID-19, the rates of outpatient healthcare visits mostly returned to pre-pandemic levels, but they remained significantly lower for individuals with cardiovascular disease, diabetes, and chronic lung disease. - Interpretation - We show that outpatient healthcare visits for older adults in most European countries declined substantially during the COVID-19 pandemic, but have since then mostly recovered back to their pre-pandemic levels. An important exception to the general recovery of healthcare visits after the pandemic is people living with chronic conditions, who have continued to utilise healthcare at lower levels than in the pre-pandemic era. Policy innovations are needed to ensure that chronic disease patients re-engage with care after major health systems disruptions. - Funding - Research in this article is a part of the European Union’s H2020 SHARE COVID-19 project (Grant Agreement No. 101015924).
Online verfügbar: 24. September 2025, Artikelversion: 7. Oktober 2025
Gesehen am 09.02.2026